4.3x+2 − 2.3x+1 = 810
3x+2+4.3x+1=7.36
\(3^{x+2}+4\cdot3^{x+1}=7\cdot3^6\\ 3^x\cdot3^2+4\cdot3^x\cdot3=5103\\ 3^x\left(9+12\right)=5103\\ 3^x\cdot21=5103\\ 3^x=243\\ 3^x=3^5\\ x=5\)
c) 4.3x+2-3x-1= 963 tìm x
\(4\cdot3^{x+2}-3^{x-1}=963\\ \Leftrightarrow36\cdot3^x-\dfrac{1}{3}\cdot3^x=963\\ \Leftrightarrow3^x=27\\ \Leftrightarrow x=3\)
\(4.3^{x+2}-3^{x-1}=963\\ \Leftrightarrow4.3^2.3^x-\dfrac{3^x}{3}=963\\ \Leftrightarrow3^x.\left(36-\dfrac{1}{3}\right)=963\\ \Leftrightarrow3^x.\dfrac{107}{3}=963\\ \Leftrightarrow3^x=27\\ \Leftrightarrow3^x=3^3\\ \Leftrightarrow x=3\)
Vậy x= 3
Đang cần gấp
A/4.3x-12.3x+2=4.36+2.39
B/1/5.2x+1/3.2x+1=1/5.27+1/3.28
a: =>\(4\cdot3^x\cdot\dfrac{1}{3}+2\cdot3^x\cdot9=4\cdot3^6+2\cdot3^9\)
=>3^x(4*1/3+2*9)=3^6(4+2*3^3)
=>3^x*58/3=3^6*58
=>3^x/3^6=3
=>x-6=1
=>x=7
b: =>\(2^x\cdot\left(\dfrac{1}{5}+\dfrac{1}{3}\cdot2\right)=2^7\left(\dfrac{1}{5}+\dfrac{1}{3}\cdot2\right)\)
=>2^x=2^7
=>x=7
Tổng các nghiệm của phương trình
3 2 x + 2 - 4 . 3 x + 1 + 3 = 0 là
A. - 1
B. 1
C. 4 3
D. 1 3
Tổng các nghiệm của phương trình 3 2 x + 2 - 4 . 3 x + 1 + 3 = 0 là
A. - 1
B. 1
C. 4 3
D. 1 3
(4.3x-4)-2=18
\(\left(4.3x-4\right)-2=18\)
\(\Rightarrow12x-4-2=18\)
\(\Rightarrow12x=24\Leftrightarrow x=2\)
(4.3x - 4) - 2 = 18
<=> 12x - 4 = 20
<=> 12x = 24
<=> x = 2
\(\left(4.3x-4\right)-2=18\)
\(\Rightarrow12x-4-2=18\)
\(\Rightarrow12x-6=18\)
\(\Rightarrow12x=24\)
\(\Rightarrow x=2\)
3^x -1 + 2.3x = 189
(2^11) + (2^10) + (2^9) + (2^3) + (2^2) + 2 + 1) + ((2^8) + (2^4) + 1) =
2.3x + 5.3x + 1 = 153
\(2.3^x+5.3^x.3=153\Leftrightarrow2.3^x+15.3^x=153\)
\(\Leftrightarrow17.3^x=153\Leftrightarrow3^x=9\Leftrightarrow x=2\)
\(\Leftrightarrow2.3^x+5.3.3^x=153\)
\(\Leftrightarrow17.3^x=3^2.17\)
\(\Leftrightarrow3^x=3^2\Rightarrow x=2\)
Giải bất phương trình 6 x + 2 x + 2 ≥ 4 . 3 x + 2 2 x